The impact of paper-based versus computerized presentation on text comprehension and memorization. (January 2016) - Porion, Alexandre; Aparicio, Xavier; Megalakaki, Olga; Robert, Alisson; Baccino, Thierry
Abstract: We compared the effects of two media (paper vs. computer) on reading comprehension and memorization among students in their third or fourth year of secondary school. To assess comprehension, we constructed and validated a text with a carefully controlled hierarchical structure, accompanied by a questionnaire containing three types of questions (surface, semantic, inference). Memory of the text was assessed with a test based on the Remember-Know (R/K) paradigm. The results of the comprehension and R/K tests indicated that there was no difference between the two media. Regardless of medium, surface comprehension was better than either semantic or inference comprehension. The R/K test indicated that memorization was better for the surface elements of the text (more R than K responses). In conclusion, overall results show that if we fulfil all the conditions of paper-based versus computerized presentation (text structure, presentation on a single page, screen size, several types of questions measuring comprehension and memory performances), reading performances are not significantly different. Highlights: The objective was to compare reading from paper versus computers. We developed a one-page text with a specific structure. We measured comprehension and memorization from paper and computer. Results did not reveal any difference between paper and computer.